STRATEGI KOMUNIKASI KODIM 1611/BADUNG DALAM SOSIALISASI KEGIATAN KOMUNIKASI SOSIAL KREATIF TAHUN 2017 - Saraswati, Widia; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2018)
ABSTRACT Indonesian Army has made various efforts and actions to create harmony with Indonesian citizens which is known as Territorial Development that is organized through Creative Social Communication activity. Current study aims to find out how the communication strategy carried out by 1611th/Badung Military District to socialize Creative Social Communication activities in 2017. This research is a qualitative descriptive study. The result analysis using four elements of Anwar Arifin: 1). The audience is determined by Command in the form of directive which are Elementary and Junior High School Students in Denpasar and Badung. 2). The message is determined based on the theme and material that is issued directly. 3). Establishing Method, by means of its execution canalizing, the form of its contents: informative and persuasive. 4). Selection of Media Use, which are using directive based on command, face-to-face and technical meeting. Keywords: Communication Strategy, 1611th/Badung Military District, Creative Social Communication